Pengaruh Intellectual Capital dan Kebijakan Dividen terhadap Nilai Perusahaan (Penelitian pada Perusahaan-Perusahaan yang Pernah Masuk ke dalam Indeks LQ45 Periode 2015-2019) - Dede Sri Rahayu (Entrepreneurship Faculty, Universitas Garut, 2021)
This research aimed to provide empirical evidence regarding the effect of intellectual capital and dividend policy on firm value. This research used the verification method, namely partial least square (PLS). This research used PLS method because the data does not have a normal distribution. The population of this research were 65 companies, while the sample used 26 companies. The sampling technique used purposive sampling technique. Based on the results of this research showed that intellectual capital had a positive effect on firm value, while dividend policy had no effect on firm value. Keywords : Firm Value, Intellectual Capital, Dividend policy, LQ45 Index, Partial Least Square